1991
DOI: 10.1007/bf00037138
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the maizerab17 gene promoter in transgenic heterologous systems

Abstract: The maize rab17 gene is expressed in different plant parts in response to ABA and osmotic stress (J. Vilardell et al., Plant Mol Biol 14 (1990) 423-432). Here we demonstrate that 5' upstream sequences of the rab17 gene confer the appropriate patterns of expression on the chloramphenicol acetyl transferase (CAT) reporter gene in transgenic tobacco plants, as well as in protoplasts derived from cultured rice cells. Specifically, a CAT construct containing a large 5' upstream fragment of rab17 (-1330/+29) results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Constructs were designed with loxP sites (in the same orientation) flanking the entire sequence containing the Wus2, Bbm, and CRE expression cassettes. To drive excision, the rab17 promoter (Vilardell et al, 1990(Vilardell et al, , 1991, a strong drought-inducible maize promoter, was used to drive expression of the CRE recombinase gene. Using desiccation to induce the rab17 promoter and CRE expression resulted in the removal of the sequences between the loxP sites ( Figure 3).…”
Section: Immature Embryo Transformation Using Agrobacteriummentioning
confidence: 99%
See 1 more Smart Citation
“…Constructs were designed with loxP sites (in the same orientation) flanking the entire sequence containing the Wus2, Bbm, and CRE expression cassettes. To drive excision, the rab17 promoter (Vilardell et al, 1990(Vilardell et al, , 1991, a strong drought-inducible maize promoter, was used to drive expression of the CRE recombinase gene. Using desiccation to induce the rab17 promoter and CRE expression resulted in the removal of the sequences between the loxP sites ( Figure 3).…”
Section: Immature Embryo Transformation Using Agrobacteriummentioning
confidence: 99%
“…Starting at the right border, the first expression cassette contained the maize Ubi promoter and intron driving expression of Am-Cyan1 (Matz et al, 1999), with a FLP-recombinase target site (FRT1) positioned between the Ubi intron and the Am-Cyan1 (CYAN) coding sequence. The next three expression cassettes contained (1) the maize rab17 promoter and 59UTR (Vilardell et al, 1990(Vilardell et al, , 1991 driving expression of moFLP (with a potato LS1 intron), (2) the nos promoter driving the Wus2 structural gene, and (3) the maize Ubi promoter and intron driving the maize Bbm gene. The last pinII sequence in this threecassette series was followed by a second FRT site and a Zs-Yellow-N1 coding sequence (YFP).…”
Section: Agrobacterium Strains and Vectorsmentioning
confidence: 99%
“…G-box elements contain the core sequence 5'-ACGT-3', a binding motif for Leu zipper proteins (Schindler et al, 1992a), and are functional in a range of plant gene promoters, primarily those regulated by UV/ visible light (Schulze-Lefert et al, 1989) or by ABA, as in the wheat Em promoter (Marcotte et al, 1989;Guiltinan et al, 1990) and the rice rabl6 promoter (Mundy et al, 1990). The ABRES from severa1 ABA-responsive genes have been characterized and shown to be G-box-like elements (Vilardell et al, 1991;Michel et al, 1993;Straub et al, 1994). The Adk G-box-1 element is identical to the ABRE identified in the Em gene.…”
mentioning
confidence: 99%
“…Many genes responsive to ABA (rab) are controlled at the transcriptional level. Functional dissection of rab promoters using transient expression assays in protoplasts has revealed the existence of a specific sequence element (ABRE) which confers ABA responsi veness upon the reporter gene (Marcotte et al 1989, Vilardell et al 1991. Moreover, leucine zipper-type proteins binding to the ABRE sequence have been identified (Guiltinan et al 1990, Oed a et al 1991.…”
mentioning
confidence: 97%
“…Moreover, leucine zipper-type proteins binding to the ABRE sequence have been identified (Guiltinan et al 1990, Oed a et al 1991. However, recent studies have shown that the expression of rab genes are also controlled by a variety of other processes and that changes in ABA levels are not always correlated with changes in gene expression (PIa et al 1991, Nordin et al 1991, Espelund et al 1992. To further investigate the role of ABA in the control of rab gene expression we have initiated a genetic approach to characterize the transcriptional regulation of the maize (ABA-responsive) rab genes by using different mutants as genetic tools.…”
mentioning
confidence: 98%